2021
DOI: 10.1136/bmj.n604
|View full text |Cite
|
Sign up to set email alerts
|

Associations of healthy lifestyle and socioeconomic status with mortality and incident cardiovascular disease: two prospective cohort studies

Abstract: Objective To examine whether overall lifestyles mediate associations of socioeconomic status (SES) with mortality and incident cardiovascular disease (CVD) and the extent of interaction or joint relations of lifestyles and SES with health outcomes. Design Population based cohort study. Setting US National Health and Nutrition Examination Survey (US NHANES, 1988-94 and 1999-2014) and UK Biobank. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
343
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 367 publications
(443 citation statements)
references
References 45 publications
16
343
3
2
Order By: Relevance
“… 28 A RERI >0 and the lower limit of 95% CI > 0 suggests a synergistic (biological) interaction. 29 , 30 Generally, the effect of baseline exposure on mortality lags for several years. Therefore, we conducted sensitivity analysis by excluding participants with <2, <5, and <10 yrs of follow-up times to examine the influence of reverse causation/confounding due to pre-existing diseases in our main findings.…”
Section: Methodsmentioning
confidence: 99%
“… 28 A RERI >0 and the lower limit of 95% CI > 0 suggests a synergistic (biological) interaction. 29 , 30 Generally, the effect of baseline exposure on mortality lags for several years. Therefore, we conducted sensitivity analysis by excluding participants with <2, <5, and <10 yrs of follow-up times to examine the influence of reverse causation/confounding due to pre-existing diseases in our main findings.…”
Section: Methodsmentioning
confidence: 99%
“…The inconsistencies in the SES and hypertension association warrant exploration of potential modifiable mediators. Lifestyle factors such as body mass index (BMI), alcohol intake, physical activity, and smoking are commonly viewed as mediators between SES and health and that healthy lifestyle might attenuate the socioeconomic inequities in health [ 26 , 27 ]. Studies from high-income countries suggest that variations in BMI, smoking, and alcohol between different SES groups [ 28 ] account for substantial proportion of inequalities in hypertension [ 10 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between socioeconomic status and CVD has been well documented in previous studies. [27][28][29] However, to the best of our knowledge, the changing pattern of socioeconomic disparities in CVD in Canada over the past decade remains unclear. In this study, we found persistent absolute and relative socioeconomic inequalities in heart disease and stroke in Canada from 2005 to 2016, and the narrowing socioeconomic inequalities were only observed for heart disease among men, suggesting a failure to achieve an equitable improvement in CVD prevalence.…”
Section: Discussionmentioning
confidence: 99%